A música sendo inspiração e referência na minha vida (e em minhas práticas) como educador e evangelizador – relato de experiência - Bernas Filho, Carlos Alberto (Universidade do Vale do Rio dos Sinos, 2025)
This Final Project consists of an Experience Report, where I tell a little about my life, which has always been (and continues to be) permeated by Music, whether in Education or in Evangelization. As Plato once said: “Music is the great medicine of the soul!” Music has always been a protagonist in my story and is part of my emotional memory. Through Music, I find motivation to continue working in the areas of Education and Evangelization. In my case, one thing is linked to the other. Working this way, within a Jesuit space, gives me pleasure and makes my life gain new meaning every day, to always better love and serve.
Keywords: Música; Memória; Amar; Servir; Educação; Evangelização; Music; Memory; Love; Serve; Education; Evangelization